Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network Update: September 2023 ... : DALAM update September 2023 ... - Campbell, Sandy (University of Alberta Library, 2023)
This is a published update of the activities of the University of the Arctic Thematic Network on Decolonization of Arctic Library and Archives Metadata (DALAM), covering the months May -September 2023. ...